A new species of Indian caecilian highlights challenges for species delimitation within Gegeneophis Peters, 1879 (Amphibia: Gymnophiona: Indotyphlidae) - Kotharambath, Ramachandran; Wilkinson, Mark; Oommen, Oommen V.; Gower, David J. (Zootaxa, 2015)
A new species of indotyphlid caecilian amphibian, Gegeneophis tejaswini sp. nov., is described based on eight specimens from lowlands of the most northerly district of the state of Kerala in the southern part of the Western Ghats region, India. This species is distinguished from all other Gegeneophis in annulation characters and genetics (> 6% different from most similar nominal species for 883 base pairs of mitochondrial 12S and 16S rRNA gene sequence data). The high degree of morphological similarity of G. krishni, G. mhadeiensis and the new species underlines that, for some Gegeneophis, larger samples and/or new characters will be needed to further advance the taxonomy of this genus.